Protection of constitutional rights against Indonesian women workers - Lestari, Sulistyani Eka (Linguistics and Culture Review, 2021)
Female Labor generates foreign exchange. Objectives: want to know among other things: (1). TKW as a supporter of foreign exchange (2). Protection of constitutional rights abroad (3). The concept of protection of female workers outside. (4). Forms of legislation and international agreements. Method: With a qualitative approach in developing research to reveal the truth systematically, it is done through (a). Type of Research (b). Research approach and (c). Data collection technique. Conclusion: (1). Law Number 39 of 2004 concerning the Placement and Protection of Workers Abroad (2). Women Workers as elements of the State, must continue to have their rights as citizens as regulated in the constitution (3). The rights of every citizen, everyone has the right to be free from discriminatory treatment, and has the right to protection.